Combination of fluorescent reagents with 2-(4-aminophenyl) benzothiazole and safranin O was useful for analysis of spore structure, indicating the diversity of Bacillales species spores - Kuwana, Ritsuko; Ito, Kiyoshi; Takamatsu, Hiromu (Frontiers in Microbiology, 2025)
BackgroundSafranin O is commonly used for the gram staining of bacteria and fluorescent staining of plant tissues. We aimed to perform a more detailed structural analysis of bacterial spores by analyzing the staining pattern of safranin O, together with a combination of other fluorescence probes, including 2-(4-aminophenyl) benzothiazole (APBT).MethodsWe stained spores from six Bacillales species, including Bacillus subtilis, B. licheniformis, Niallia circulans, Brevibacillus brevis, Lysinibacillus sphaericus, and Paenibacillus polymyxa, with safranin O and APBT and observed them using fluorescence microscopy. We also performed comparative analysis using other fluorescent reagents, including auramine O, rhodamine B, thioflavin T, and congo red. Additionally, the localization of spore proteins was analyzed by green fluorescent protein (GFP)-fused strains and spore-forming-defective mutant strains of B. subtilis.ResultsFluorescence microscopy analysis revealed that safranin O exhibits two distinct fluorescence peaks, green and red, in Bacillales species in different regions of the spore structure, indicating the complexity and diversity within the spore structures. APBT fluorescence co-localized with specific spore structures and aligned with the GFP fused strains, which were used as marker proteins for the spore structural components, such as the outermost spore layer (crust), inner spore coat, cortex, and inner spore membrane. Safranin O red fluorescence was detected near the inner spore coat, congo red, and thioflavin T fluorescence. In contrast, the green fluorescence regions were similar to those identified by APBT, auramin O, and rhodamine B. Spore morphogenesis-deficient mutants, including spoIVA and cotE, exhibited altered fluorescence patterns with APBT and safranin O, indicating abnormal spore structures and staining of forespore periphery.ConclusionThese findings show that safranin O produces distinct red and green fluorescence patterns in bacterial spores. The combined use of safranin O and other fluorescent probes with fluorescence microscopy and GFP fusion proteins offers a powerful approach for visualizing and analyzing bacterial spore structures. The present study on Bacillales spores may have broad applications in environmental microbiology, food safety, and biosecurity. It may provide a framework for rapid detection of spore-forming bacteria during industrial fermentation and antimicrobial drug development.